Python wu jian du xue xi = Hands-on unsupervised learning with Python / = Hands-on unsupervised learning with Python - Bonaccorso, Giuseppe (Ren min you dian chu ban she = Posts & Telecom Press, 2020)
Detailed summary in vernacular field.
880-05;Ben shu you Yingguo Packt Publishing gong si shou quan Ren min you dian chu ban she chu ban
Keywords: Python (Computer program language); Artificial intelligence; Machine learning; Python (Langage de programmation); Intelligence artificielle; Apprentissage automatique; artificial intelligence